Interdisciplinary Research and Classification Problems:A Case Study - Neelameghan, A. (Journal of Information and Knowledge, 1974)
Interdisciplinary associations lead to the emergence of hybrid disciplines. Interdisciplinary association may be of two types - multi-disciplinary association and interdisciplinary borrowing. Multi-disciplinary association may be juxtaposition studies or convergence of view points. Interdisciplinary borrowing involves borrowing of techniques and tools, or borrowing of data, or use of principles and theories. The emergence of hybrid discipline pose problems in classification. Some of these problems are highlighted by taking the newly emerging discipline of cycle research as a case study. Cycle research is a general theoretical study of cycle phenomenon. It can be deemed to be formed by either of the two modes of formation namely distillation and clustering. In Colon Classification, ed 7, Cycle Research may be accommodated in the schedule of Personality Isolates in the Basic Subject BTM Time Series Analysis.